2020
DOI: 10.1097/md.0000000000021897
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic red blood cell transfusion is an independent risk factor for 1-year mortality in elderly patients undergoing femoral neck fracture surgery

Abstract: Allogeneic red blood cell transfusion (ABT) is 1 of the poor prognostic factors for morbidity and mortality in patients with hip fracture, particularly among elderly patients. This study aimed to investigate the risk factors for ABT and 1-year mortality in elderly patients undergoing surgery for femoral neck fracture. A total of 225 elderly patients who underwent femoral neck fracture surgery between May 2013 and November 2015 at a tertiary medical center were retrospectively recruited. Medical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Though blood transfusion may be necessary in managing acute blood loss following surgery, it is not without its risks. For instance, blood transfusion following surgery for femoral neck fractures has been associated with an increased risk of infection and has been shown to be an independent risk factor for mortality at 1 year [ [24] , [25] , [26] ]. As such, efforts to avoid transfusion should be made.…”
Section: Discussionmentioning
confidence: 99%
“…Though blood transfusion may be necessary in managing acute blood loss following surgery, it is not without its risks. For instance, blood transfusion following surgery for femoral neck fractures has been associated with an increased risk of infection and has been shown to be an independent risk factor for mortality at 1 year [ [24] , [25] , [26] ]. As such, efforts to avoid transfusion should be made.…”
Section: Discussionmentioning
confidence: 99%
“…Among of them, the higher rate of transfusion deserves special mention. Previous studies have reported that allogeneic transfusion was a predictor for 1-year mortality in elderly patients with surgically treated FNF [ 30 ]. In addition, hypoalbuminemia and AAC ≥ 6 were also identified as independent risk factors ( P = 0.041, P = 0.040, respectively) for 1-year mortality in multivariate analysis, which was consistent with previous studies [ 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that blood transfusion increased the incidence of complications and led to blood shortages, prolonged hospital stays, and increased hospital costs ( Dai et al, 2020 ; Shin et al, 2020 ). For elderly FNF patients undergoing HA, these problems cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%